Which Factors Affect Pregnancy Until Calving and Pregnancy Loss in Buffalo Recipients of in vitro Produced Embryos? - Saliba, Wilson Pardini; Gimenes, Lindsay Unno [UNESP]; Drumond, Roberti Martins; Bayao, Henrique Xavier Salgado; Di Palo, Rossella; Gasparrini, Bianca; Rubessa, Marcello; Baruselli, Pietro Sampaio; Sales, Jose Nelio Souza; Bastianetto, Eduardo; Leite, Romulo Cerqueira; Alvim, Mucio Tulio Teixeira (Frontiers Media Sa, 2020)
In vitro embryo production and embryo transfer (ET) in buffaloes has been developed for decades. However, most studies are focused on the donor or laboratory improvements, and there is a lack of reports regarding the recipients. Therefore, our aim was to investigate factors associated to pregnancy (P/ET), pregnancy loss (PL), and calving rates in buffalo recipients. The studied factors were season, recipient parity, the synchronization protocol, the CL diameter, asynchrony between the embryo and the recipient, the day of the recipient estrous cycle, the embryo (fresh vs. vitrified), the day of embryo development, and the embryo stage. These retrospective data, from a program of in vitro produced embryos, were analyzed by logistic regression, and the odds ratio was also estimated. Two factors were related to P/ET and the calving rate: (1) progesterone associated to estradiol plus eCG protocol for fixed time ET tended to affect positively P/ET on day 30 (41.9 vs. 36.1%, respectively; P = 0.07; AOR = 1.28) and P/ET on day 60 (37.8 vs. 36.1%, respectively; P = 0.09; AOR = 1.08) compared to the Ovsynch protocol; and (2) the CL diameter (>= 14.5 mm) at transfer increased P/ET on day 30 (47.4 vs. 32.5%; P < 0.01; AOR = 1.87) and on day 60 (45.3 vs. 27.7%; P < 0.01; AOR = 2.16), and also the calving rate (37.9 vs. 21.7%; P < 0.01; AOR = 2.20). PL was greater when ET was done in the nonbreeding season compared to the breeding season (PL 30-60: 12.8 vs. 0.0%, P = 0.01; AOR > 999.99; PL 60-calving: 26.8 vs. 3.6%, P = 0.03; AOR = 9.90; and PL 30-calving: 36.2 vs. 3.6%, P = 0.01; AOR = 15.30). In conclusion, the data of our study indicated that the synchronization protocol, the CL diameter, and ET during the breeding season impacted the reproductive efficiency of buffalo recipients.
Keywords: embryo transfer; OPU; IVEP; fresh embryos; vitrification; embryo; fetal mortality